n-6=-283/4

Simple and best practice solution for n-6=-283/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-6=-283/4 equation:



n-6=-283/4
We move all terms to the left:
n-6-(-283/4)=0
We get rid of parentheses
n-6+283/4=0
We multiply all the terms by the denominator
n*4+283-6*4=0
We add all the numbers together, and all the variables
n*4+259=0
Wy multiply elements
4n+259=0
We move all terms containing n to the left, all other terms to the right
4n=-259
n=-259/4
n=-64+3/4

See similar equations:

| x+(x+2)+(x+4)=87 | | X/2+4x=9/2x | | (30k-48)-20=(22k-33)+3k | | 7^9x=15 | | 5x-4=28+1x | | n=169 | | (x-4)/7=10 | | 3x=0.50x+20 | | 5x=60= | | 16x+4=-4x | | 3(4x+6)/6=9 | | 9(m+10)=5(m-16) | | x3+4x2+13x=0 | | 10b-6(5+2b)=-30 | | 4(x-3)=88/11 | | 7p+5=-5-9(p-2) | | -5a+10+8a=2a-4a | | -.02x+.1(x+400)=56 | | 1/3x+1/2=-1 | | 3^4p=52 | | 34x+5x+6x+15x+12x+48=x | | 24-8b=-8(b-3) | | -13+4a=-17 | | 9(m+10)=(m-16) | | x^2−6x=16 | | 5u-2=-27 | | 8(t+8)=12 | | 34+x-5=26 | | 6y^2-108=0 | | 2/9+z=28 | | m/9+14=12 | | 20(17+x)=50 |

Equations solver categories